An integrated model of human trafficking response in the prosecution process: restorative justice, therapeutic jurisprudence, survivor centered practice and anti-oppressive practice - Nichols, Andrea J. (Crime, law and social change, 2024)
A small body of research spanning more than a decade finds that survivors of human trafficking may not want to prosecute their traffickers for myriad reasons. An integrated framework combining principles of therapeutic jurisprudence, survivor centered practice, anti-oppressive practice and restorative justice provides an important theoretical lens for examining and offering alternatives to traditional prosecution in human trafficking cases. Specifically, this theoretical essay aims to draw attention to prosecutorial challenges in human trafficking cases and argues for an alternative or enhancement to traditional prosecution. Alternatives that are discussed emphasize the following: mitigating revictimization; supporting survivors’ input, aims and goals; providing opportunities for therapeutic moments, repairing harm, and restitution; and incorporating cultural humility and cultural competency in the prosecution process.